A Analisis tingkat kebugaran jasmani peserta didik di SMKN 1 Krangkeng - Muhammad Aldi; Nur Mahfuzah Agustin; Riki Ramadhan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the level of physical fitness of grade XI students at SMK Negeri 1 Krangkeng and identify factors that influence fitness. The background of this study departs from the importance of physical fitness in supporting health, learning concentration, and student readiness to face the world of work, but there is still minimal data and attention to the condition of student fitness in the school. This study uses a quantitative descriptive method with test techniques. The sample in this study amounted to 53 students selected from grade XI through a purposive sampling technique. The data collection instrument used the Indonesian Physical Fitness Test (TKJI) which includes five items: 60 meter run, pull-up, sit-up, push-up, and vertical jump. Data were analyzed using descriptive statistics, including the calculation of the average, standard deviation, and frequency. The results showed that most students had physical fitness levels in the, moderate categories.